The impact of oil palm plantation on ecology of rambutan (Nephelium lappaceum) insect pollinators - SYARIFUDDIN SYARIFUDDIN; ELIDA HAFNISIREGAR; JASMI JAMBAK; CICIK SURYANI (Society for Indonesian Biodiversity, 2018)
Syarifuddin, Hafnisiregar E, Jambak J, Suryani C. 2018. The impact of oil palm plantation on ecology of rambutan (Nephelium lappaceum) insect pollinators. Biodiversitas 19: 1347-1351. The establishment of oil palm plantation in Sumatra was the result of massive conversion of its rainforest. Many studies have shown that oil palm plantation is a main threat to biodiversity including insect pollinators. However, its effect on the ecology of insect pollinators is still poorly studied. In this study, we investigated the impact of oil palm plantation on the species richness and composition, abundance as well as pattern of time period and duration of insect visit on rambutan, Nephelium lappaceum, flowers. Insect visitors of flowers were compared between rambutan grown in the Oil Palm Plantation (OPP) ecotone and the one in the mixed Oil Palm Garden Forest (OPGF) ecotone. Number of visiting insects on each pannicle in ten minutes period and number of flowers and pannicles visited within 2 minutes were enumerated. The length of time of a randomly selected individual of the most abundant insects visited a flower and a pannicle was also recorded. The results showed that species composition of insect visitors was different between the two ecotones and total insect abundance was significantly higher on rambutan flowers located in the OPGF ecotone compared to rambutan trees grown close to oil palm plantation. The insect visitors on rambutan flowers in the OPGF ecotone were dominated by bees while in the OPP was dominated by Calliphorid fly. Among the main pollinators, the bee Apis cerana visited far more flowers and pannicles compared to Trigona sp and Chrysomya sp. Thus, more evidence showing that oil palm plantation probably has caused the disappearance of main species of bee pollinators, reduced abundance of flower-visiting insects, change of pollinator species composition, change of the pattern of time and change the duration of insect visit of rambutan flowers.